Ce que l’(agro)écologisation des projets de recherche produit sur différentes catégories professionnelles et leurs interactions au sein d’INRAE : étude de cas à partir du projet LAPOESIE - Floriane Derbez; Evelyne Lhoste; Myriam Grillot (VertigO)
This case study aims to examine how agro-ecological and interdisciplinary framework transforms research objects and recomposes professional identities within the French national research institute INRAE. We are interested in how the project affects the staff of two "specialized" research units, one in plant production (fruit arboriculture), the other in animal production (rabbit farming). In line with science and technology studies, the article shows on the one hand that people committed to agroecology develop "deviant" research practices in relation to their disciplinary scientific socializations, and on the other hand face institutional obstacles linked to the organization of the institute and the compartmentalization between plant and animal production. The project's agro-ecological and interdisciplinary framework thus generates a number of shifts, frictions and recompositions leading to changes in the way research is perceived and carried out as well as the professions associated with it.